Ecuadorian students’ perception on the use of translation in the EFL classroom - Matt William Payne; Juan Pablo Contreras (Studies in English Language and Education, 2019)
For over half a century, the upward trend to rather demonize the use of the first language (L1) has led to its complete disregard and interdiction by many language institutions around the world due to the ever-so-trendy idea that any use of the L1 will be seen as counter-productive and even damaging to one’s intent on the acquisition of the second language (L2) (Carreres, 2006). Therefore, the purpose of this study is to demonstrate what students believe as beneficial or unfavorable when it comes to using translation in the classroom either by the teacher, the students themselves or within the lesson in general. A total of 115 Ecuadorian students were surveyed with simple true or false statements regarding their opinion on translation. The students were arranged in two groups: A1 level and B1 level students. The answers from the survey were then averaged out in percentage form. The study suggests that there are indeed different opinions as to the use of translation in class. However, in general, it is perceived that lower-level students believe that normal use of translation in the classroom is a good method of or essential to learning, while most upper-level students prefer either solo use of the L2 or at least minimal use of the L1 in class.